RELATIONSHIP BETWEEN THE PERCEPTION OF CORRUPTION AND TAX EVASION IN LATIN AMERICA - Lima, Lauro Vinício de Almeida; Silva, Vanessa Karla Rebouças da; Lucena, Wenner Gláucio Lopes (Advances in Scientific and Applied Accounting, 2022)
Objective: The research aimed to verify the implication of the level of perception of corruption, in the public sector, in tax evasion of taxes on company income in Latin American countries. Method: With data from 10 Latin American countries, between 2011 and 2017, in a sample of 771 companies and 5006 observations, initially, in the study, the tax evasion proxy was estimated, through the book tax difference abnormal, as a result of the residue of a regressive model that considered the variables that would explain, on average, the difference between tax and accounting income. Then, the BTDA was regressed with the variables of corruption perception of the tax rate on profit required in the country. Results: The results found indicate that society’s perception of corruption in the public sector can stimulate tax evasion in companies in the face of the feeling of abandonment and social neglect and that high tax rates on profit discourage tax evasion due to the possibility of companies receiving high fines for non-payment of taxes. Contributions: The research advances the debate on government corruption and its influence on the behavior of managers in companies, finding evidence of a direct relationship between the perception of corruption in the public sector and tax evasion in publicly traded companies in Latin American countries. These findings contribute to the understanding of the determining reasons for tax evasion practices in companies, providing explanations that clarify in a practical way how corruption in the public sector can influence the private sector.